An Ion‐Exchange Promoted Phase Transition in a Li‐Excess Layered Cathode Material for High‐Performance Lithium Ion Batteries. Issue 9 (5th February 2015) - Zhao, Jianqing; Huang, Ruiming; Gao, Wenpei; Zuo, Jian‐Min; Zhang, Xiao Feng; Misture, Scott T.; Chen, Yuan; Lockard, Jenny V.; Zhang, Boliang; Guo, Shengmin; Khoshi, Mohammad Reza; Dooley, Kerry; et al.
<x xml:space="preserve">Abstract</x> A new approach to intentionally induce phase transition of Li‐excess layered cathode materials for high‐performance lithium ion batteries is reported. In high contrast to the limited layered‐to‐spinel phase transformation that occurred during in situ electrochemical cycles, a Li‐excess layered Li[Li0.2Mn0.54Ni0.13Co0.13]O2 is completely converted to a Li4Mn5O12‐type spinel product via ex situ ion‐exchanges and a post‐annealing process. Such a layered‐to‐spinel phase conversion is examined using in situ X‐ray diffraction and in situ high‐resolution transmission electron microscopy. It is found that generation of sufficient lithium ion vacancies within the Li‐excess layered oxide plays a critical role for realizing a complete phase transition. The newly formed spinel material exhibits initial discharge capacities of 313.6, 267.2, 204.0, and 126.3 mAh g−1 when cycled at 0.1, 0.5, 1, and 5 C (1 C = 250 mA g−1), respectively, and can retain a specific capacity of 197.5 mAh g−1 at 1 C after 100 electrochemical cycles, demonstrating remarkably improved rate capability and cycling stability in comparison with the original Li‐excess layered cathode materials. This work sheds light on fundamental understanding of phase transitions within Li‐excess layered oxides. It also provides a novel route for tailoring electrochemical performance of Li‐excess layered cathode materials for high‐capacity lithium ion batteries.